Optimization of Wood Powder Particle Size and Weight Fraction for Enhancing the Mechanical Properties of Wood Plastic Composites Using Recycled EPS Matrix - Cahyo Budiyantoro; Sudarisman; Aris Widyo Nugroho; Zaenul Ilyas; Bastian Bilyferdin (Journal of Applied Science and Engineering, 2025)
Indonesia’s abundant wood powder waste is underutilized, much like expanded polystyrene (EPS) plastic waste. This research explores combining wood powder with EPS to produce wood plastic composite (WPC) and examines how different wood powder types affect its mechanical properties. WPC specimens were produced using pine, sengon, and teak wood powders with particle sizes of 20,40 , and 60 mesh and weight fractions of 5%, 10%, and 20%. The Taguchi method was employed to design an orthogonal array, and SN/Ratio and ANOVA were used to analyze the influence of factors on flexural strength and impact toughness. The results show that sengon wood powder with a particle size of 60 mesh and a weight fraction of 20% achieves the highest flexural strength. Meanwhile, sengon wood powder with a 60− mesh size and a 5% weight fraction yields the best impact strength. This study demonstrates the potential for improving WPC properties by using wood waste as a filler.